2017
DOI: 10.1075/japc.27.1.03idi
|View full text |Cite
|
Sign up to set email alerts
|

Examining political efficacy among Malaysian voters

Abstract: The technological advancement and political situations have dramatically impacted the way traditional and new media have played their role in society, especially in the political development of the country. Studying media use and credibility have been a major concern among scholars to understand audience perceptions and attitudes towards the media and their role in politics. This study investigated the level of media use and credibility among voters and their perception of political efficacy. Drawing on a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Складно ідентифікувати норманів, що діяли в Іспанії. Згідно християнським джерелам, ім'я ватажка тих з них, хто діяв у 960-х роках у Галісії Гундеред 68 . А. Христіс вважає його сином норвезького короля Гаральда Прекрасноволосого 69 .…”
Section: взаємозв'язок вторгнень скандинавів на піренейській півострі...unclassified
“…Складно ідентифікувати норманів, що діяли в Іспанії. Згідно християнським джерелам, ім'я ватажка тих з них, хто діяв у 960-х роках у Галісії Гундеред 68 . А. Христіс вважає його сином норвезького короля Гаральда Прекрасноволосого 69 .…”
Section: взаємозв'язок вторгнень скандинавів на піренейській півострі...unclassified
“…He found two motives of political information seeking, namely diversion and vote guidance, significantly correlated with political efficacy. In addition, scholars have concluded that people who believe they are competent to participate in politics are motivated to consume political news and participate in politics Idid et al, 2017;Pingree, 2011). Equally, scholars have averred that the association between Internet/social media use and political participation will be stronger for those who already have high levels of political efficacy (Chan & Guo, 2013).…”
Section: Political Efficacy As a Moderatormentioning
confidence: 99%
“…According to Idid et al (2017), people consider traditional media (i.e. TV, newspaper and radio) as the credible source for information, whereas the internet is ranked as the least credible source.…”
Section: Introductionmentioning
confidence: 99%